(untitled) (Gaceta Técnica, 2024)
The research article presented deals with the experimental design adding ash and fiber from Gallus Domesticus. Methods from similar applications were reviewed to obtain optimal dosages of ash at 0.5%CGD, 1.0%CGD and 2.0%. CGD, on the other hand, in the fibers was 0.2%FGD, 0.5%FGD and 1.0%FGD instead. In order to improve the properties of the concrete, they were evaluated in a fresh and hardened state, performing compression and bending tests at 7, 14 and 28 days, analyzing three samples for each design, in this case ash and fiber were added according to the cement weight. the objectives, the temperature, workability and unit weight test was carried out, and it was also verified after 28 days, observing with the latter that with the addition of 0.5%CGD and 0.2%FGD maximum results were obtained. compression of 37.51MPa, exceeding the standard design by 4.15%, on the other hand, in the flexural strength with the addition of 1.0%FGD and 0.5%FGD The maximum resistance of 6.03MPa was obtained, having an increase of 27.35% compared to the standard design